ANALISIS EFEKTIVITAS STRATEGI SALES PROMOTION TERHADAP VOLUME PENJUALAN MIE SEDAAP PADA PT MUNCUL JAYA SENTOSA, DI KABUPATEN MIMIKA, PROVINSI PAPUA (2016-2018) - Zulfiana Zulfiana; Tri Apriyono (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2022)
This study aims to analyze the effectiveness of sales promotion strategies carried out by PT Muncul Jaya Sentosa to increase the sales volume of delicious noodles. In this study using the epic model effectiveness measurement method, where the effectiveness measurement is divided into 4 dimensions, namely the dimensions of empathy, impact, persuasion, and communication.